UPAYA PENINGKATAN NILAI ESTETIK AKSESORI BUSANA DARI BAHAN TEMPURUNG KELAPA - Enny Zuhni Khayati (SURYA SENI, 2007)
Fashion accessories made from coconut shells that is unique,  distinguishable, and simpel have a limited function, hence the customer does not like it. This research  was made of ﬁ nd any alternatives to improve the aestethic value of fashion accessories made from coconut shells and also to ﬁ nd the  interest rate of consumer towards the application of the  coconut shells accessories  design.This research was done by using quasi experiment approach to make the sample consists of three sets of fashion accessories (necklace, bracelet and earrings) that are different in style and form. To ﬁ nd the interest rate of the consumer, survey was done towards female consumers. The sample taking was being done accidentally and we got 75 responders. The data  was gathered with questionaire technique ﬁ lled when the responders looked at the sample of fashion accessories made from coconut shells.The result of the research shows that to improve the aestethic values of the fashion accessories  made from coconut shells can be done by giving more modern details and the plays of the color that has a parallel tone with the occasion.Beside, the interest rate of the consumer towards the fashion accessories made from coconut shells is considered high. In a rank, the application of the accessories that consumers like the most is the accessories with the basic shape ofa ros, supported with pearl beads in salmon pink; have a feminin style, classy and etnically modern. The second one is the accessories with the basic shape if diamondcompleted with a spiral-look capper wire as its supporting matter. It has a style of simpel, casual and trendy.The last is the accessories with the basic shapeof oval with a creamy brown sea shell as its supporting matter,and has a style of traditional and classic.Keywords: Aestethic value, the consumer’s interest rate, fashion accesso- ries, and coconut shells.